Curriculum Simplification and Subject Reduction to Improve the Quality of Education in Indonesia - Rachman, Taofik Andi; Latipah, Euis; Supiana; Zaqiah, Qiqi Yuliati (International Conference on Elementary Education, 2022)
The Indonesian curriculum is considered to have too many subjects. Indonesian students also do not focus on mastering the expected competencies. Finally, Indonesia has always failed in the international level assessment of PISA during its implementation. In fact, it is stated that Indonesian students need one hundred years to match the sophistication level of students' thinking from the average student of PISA participating countries if Indonesia continue to use the same education. The OECD as the organizer of PISA encourages changes in the education system for Indonesia in order to improve the quality of international-class education. One of the concerns in Indonesian education is the burden of many subjects. The purpose of this study is to describe several arguments for simplifying the curriculum and reducing the subjects in elementary schools in improving the quality of Indonesian education based on expert opinion, research and experience of educational performance in other countries. This article is a position paper to scientifically strengthen an opinion. Qualitative methods are used in this study where data are compiled, analyzed, and concluded. The results of the study indicate that curriculum simplification is necessary to focus students' competence and improve the quality of education. This study proposes several arguments that strengthen this effort, namely not all curriculum content must be a subject, cognate curriculum content can be integrated, many subjects become a burden on students, and so on. So, with this argument it will strengthen the desire to simplify the curriculum in elementary schools.